Magnetic properties of deuteric hematite in young lava flows from Iceland (Dataset) ... - Huiling Li; S. J. Beske-Diehl (Magnetics Information Consortium (MagIC), 2023)
Paleomagnetic, rock magnetic, or geomagnetic data found in the MagIC data repository from a paper titled: Magnetic properties of deuteric hematite in young lava flows from Iceland ...